Determinants of financial performance of listed firms manufacturing food products in Vietnam: regression analysis and Blinder–Oaxaca decomposition analysis - Nhung Le Thi Kim; Daphné Duvernay; Huyen Le Thanh (Journal of Economics and Development, 2021)
Purpose – This article studies the impact of micro and macro factors on firm performance in the context of an emerging economy just changed from a subsidized economy to a market economy. Design/methodology/approach – The authors carried out an investigation into 30 listed food processing companies in Vietnam from 2014 to 2019. The data are analyzed by using STATA software. In this study, beside the regression analytical technique, the Blinder–Oaxaca decomposition analysis is used to study more deeply the effect of variables on financial performance of food processing companies, so its results are reliable base to give suggestions. Findings – The results of empirical research help us to have some following conclusion. First, two variables consisting of total assets turnover ratio (ATR) and growth in sales significantly influence financial performance, when it is measured by return on equity (ROE) or return on sales (ROS). Second, leverage significantly negatively impacts return on sale. Third, there are difference in financial performance and the effect of predictors on dependent variable “ROS” between state-owned enterprises (SOEs) and non SOEs, and the causes come from the component effect. Originality/value – In fact, although a range of previous researches on that topic have been carried out, none of them dig deeper reasons resulting to the differences in financial performance between SOEs and non SOEs, whereas Vietnamese economy has just changed to a market economy since 1986, making impacts of State ownership totally different from other countries. In this study, the authors use the t-test and analysis to have more accurate conclusions about that problem.